Present and Future of Rainfall in Antarctica. Issue 8 (22nd April 2021) - Vignon, É.; Roussel, M.‐L.; Gorodetskaya, I. V.; Genthon, C.; Berne, A.
Abstract: While most precipitation in Antarctica falls as snow, little is known about liquid precipitation, although it can have ecological and climatic impacts. This study combines meteorological reports at 10 stations with the ERA5 reanalysis to provide a climatological characterization of rainfall occurrence over Antarctica. Along the East Antarctic coast, liquid precipitation occurs 22 days per year at most and coincides with maritime intrusions and blocking anticyclones. Over the north‐western Antarctic Peninsula, rainfall occurs more than 50 days per year on average and the recent summer cooling was accompanied by a decrease of −35 annual rainy days per decade between 1998 and 2015 at Faraday‐Vernadsky. Projections from seven latest‐generation climate models reveal that Antarctic coasts will experience a warming and more frequent and intense rainfall by the end of the century. Rainfall is expected to impact new regions of the continent, increasing their vulnerability to melting by the preconditioning of surface snow. Plain Language Summary: Given the cold temperatures prevailing across the continent, most precipitation over Antarctica falls as snow. Nonetheless, infrequent rainfall events have already been observed causing serious damage to penguin colonies and facilitating the melting of the snow on the ground surface. Here, we provide the first climatological characterization of rainfall occurrence over Antarctica by examining reports of visual meteorological observations at 10 Antarctic stations. We can evidence the contrast between the coasts of East and West Antarctica that experience a few days per year with liquid precipitation and the western part of the Antarctic Peninsula where rainfall occurs more than 50 days per year on average. The latter region also experienced a significant decrease in rainfall occurrence during the first 15 years of the 21st century. Simulations with latest generation numerical climate models further reveal that the Antarctic continent is projected to undergo an overall warming accompanied by more frequent and more intense rainfall events at the end of century. Rainfall is also expected to impact regions of the continent that currently do not receive rainfall, making them vulnerable to intense events of surface snow melting preceded by liquid precipitation. Key Points: First climatological characterization of rainfall occurrence in Antarctica based on meteorological reports and atmospheric reanalyses Rain events generally coincide with a warm and moist maritime intrusion and a blocking anticyclone CMIP6 scenarios suggest that the overall future warming of Antarctica will be accompanied by more frequent and more intense rainfall events